The Relationship between Students’ Vocabulary Mastery and Recount Writing Skill - Fajar Erlangga; Natalia Tri Astuti; Adhityo Kuncoro (UICELL, 2020)
The study is conducted to show the relationship between vocabulary mastery and recount writing skill among students. The study uses a survey method with the samples of 42 eleventh grade students that are randomly selected from four different classes at SMKN in Serang. The collection of data is conducted by administering multiple-choice questions and writing tests. The data are then analyzed by using regression and correlation analysis. The result of study shows that vocabulary mastery of students has a significant effect on their recount writing skill, as seen by the score of sig 0.000 < 0.05 and tO 6.606. In conclusion, there is a significant relationship between vocabulary mastery and student’s recount writing skill.